2018
DOI: 10.1177/1120700018772163
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Vancouver B2 and B3 periprosthetic femoral fractures after total hip arthroplasty in elderly patients

Abstract: Although we reported good results of fracture healing, there were functional impairment and a high rate of complications, especially dislocation, in Vancouver B2 and B3 periprosthetic fractures in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 20 publications
7
40
1
2
Order By: Relevance
“…Infection rates in revision surgery are higher than in primary arthroplasty, ranging between 2% to 7% as reported in cases of femoral revision for PFF. 8,12,16,21,23,36,37 When treating periprosthetic fractures, the reoperation rate is reported to be high: 29 in our series it is around 12%. Chatziagorou et al 35 found that the reoperation rate did not statistically differ between cementless modular (16.2%), cementless monoblock (13.6%) and cemented stems (13.2%); in cementless stems the major reason for reoperation was hip dislocation (modular 5.4%; monoblock 6.8%), while in cemented stem it was nonunion.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Infection rates in revision surgery are higher than in primary arthroplasty, ranging between 2% to 7% as reported in cases of femoral revision for PFF. 8,12,16,21,23,36,37 When treating periprosthetic fractures, the reoperation rate is reported to be high: 29 in our series it is around 12%. Chatziagorou et al 35 found that the reoperation rate did not statistically differ between cementless modular (16.2%), cementless monoblock (13.6%) and cemented stems (13.2%); in cementless stems the major reason for reoperation was hip dislocation (modular 5.4%; monoblock 6.8%), while in cemented stem it was nonunion.…”
Section: Discussionmentioning
confidence: 48%
“…An increased risk of dislocation is reported in patients with abductor mechanism insufficiency 38 or in patients with a mean subsidence of 4 mm compared to those with a mean subsidence of 0.89 mm. 36 Another important complication is periprosthetic infection; we reported 2 (8%) cases of infection. Infection rates in revision surgery are higher than in primary arthroplasty, ranging between 2% to 7% as reported in cases of femoral revision for PFF.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…All patients had achieved fracture union by the final follow-up, and the length of femoral stem fixation beyond the distal end of the fracture was greater than 4 cm, which matched well with the femur. The patients in our study achieved better clinical outcomes compared to those in previous studies, 11,33 37 such as Harris Hip score (Table 5). Further studies with larger sample sizes will be required to determine whether this method will be effective for routine treatment of Vancouver type B2 PFFs.…”
Section: Discussionsupporting
confidence: 42%
“…Our study involves longer follow-up (102 ± 24.5 months) than most previous studies, which followed up for 14.5–60 months. 11,33 37 Nevertheless, our study still has several limitations. First, the sample is relatively small, so statistical power is low.…”
Section: Discussionmentioning
confidence: 91%